The home [videorecording (DVD)] - Demonaco, James; Cantor, Adam; Cantor, Adam; Whitehead, Nathan, 1977-; Glover, John, 1944-; Phillips, Ethan; Altman, Bruce; Burse, Denise, 1952-; Rudin, Stuart; Schmidt, Nathalie; Peil, Mary Beth; Williams, Victor; et al. (Lionsgate, 2025)
A troubled man who starts working at a retirement home soon realizes its residents and caretakers harbor sinister secrets. As he investigates the building and its forbidden fourth floor, he starts to uncover connections to his own past.